Increased Hemodynamic Load in Early Embryonic Stages Alters Myofibril and Mitochondrial Organization in the Myocardium - Midgett, Madeline; López, Claudia S.; David, Larry; Maloyan, Alina; Rugonyi, Sandra (Frontiers in Physiology, 2017)
Normal blood flow is essential for proper heart formation during embryonic development, as abnormal hemodynamic load (blood pressure and shear stress) results in cardiac defects seen in congenital heart disease. However, the detrimental remodeling processes that relate altered blood flow to cardiac malformation and defects remain unclear. Heart development is a finely orchestrated process with rapid transformations that occur at the tissue, cell, and subcellular levels. Myocardial cells play an essential role in cardiac tissue maturation by aligning in the direction of stretch and increasing the number of contractile units as hemodynamic load increases throughout development. This study elucidates the early effects of altered blood flow on myofibril and mitochondrial configuration in the outflow tract myocardium in vivo. Outflow tract banding was used to increase hemodynamic load in the chicken embryo heart between Hamburger and Hamilton stages 18 and 24 ( 24hrs during tubular heart stages). 3D focused ion beam scanning electron microscopy analysis determined that increased hemodynamic load induced changes in the developing myocardium, characterized by thicker myofibril bundles that were more disbursed in circumferential orientation, and mitochondria that organized in large clusters around the nucleus. Proteomic mass-spectrometry analysis quantified altered protein composition after banding that is consistent with altered myofibril thin filament assembly and function and mitochondrial maintenance and organization. Additionally, pathway analysis of the proteomics data identified possible activation of signaling pathways in response to banding, including the renin-angiotensin system. Imaging and proteomic data combined indicate that myofibril and mitochondrial arrangement in early embryonic stages is a critical developmental process that when disturbed by altered blood flow may contribute to cardiac malformation and defects.